Retrospective study on the productive performance of Sahiwal x Friesian crossbred dairy cows / Navin Kumar Nadarajah and Nur Hardy Bin Abu Daud - Nadarajah, Navin Kumar; Abu Daud, Nur Hardy (Universiti Teknologi MARA, Sabah, 2020)
A retrospective study was carried out at one selected dairy farm located in Keningau, Sabah in order to evaluate the effect of age at first calving (AFC) on the productive performance of the primiparous Sahiwal x Friesian crossbred dairy cows. The retrospective data was collected from 123 Sahiwal x Friesian crossbred dairy cows. AFC was classified into 7 groups such as: ≤22; 23-24; 25-26; 27-28 months old; 29-30; 31-32 and >32 months old, respectively. The productive performance parameters that were evaluated consisted of the first-lactation milk yield, lactation length, average daily milk yield and dry period. Cows with AFC of 23-24 and 25-26 months of age showed the highest first lactation milk yield, 7210.14± 384.84 litres and 7053.80± 342.98 litres, respectively. Cows with AFC of 23-24 months old have also showed the longest lactation length of 410.25± 19.51 days. However, cows with AFC of 23-24 months of age produced the least average daily milk yield, that was about 17.62± 0.60 litres/day and cows that were calved at 29-30 months of age and >32 months of age produced the highest average daily milk yield, that was about 24.10± 0.94 litres/day and 24.16± 0.79 litres/day, respectively. The study showed that AFC had a significant effect on the first lactation milk yield, lactation length and average daily milk yield of the Sahiwal x Friesian crossbred dairy cows (p<0.05). However, it was found that AFC had no significant effect on the dry period (p>0.05). Overall, cows with the AFC of 23-24 months old have showed the best productive performance.